THE IMPACT OF AGED 6 ON LANGUAGE ACQUISITION: A PSYCHOLINGUISTIC STUDY OF FIRST AND SECOND LANGUAGE LEARNERS - Tifani, Juliana; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2024)
This study investigates the psycholinguistic impact of age on language acquisition in children aged 6-12, focusing on both first (L1) and second language (L2) learners Middle childhood is a critical phase in cognitive and linguistic development, marked by significant brain maturation and increasing cognitive abilities. For L1 learners, this period involves mastering complex syntactic structures, expanding vocabulary, and refining communicative competence. L2 learners benefit from greater cognitive flexibility than older learners, although they may require more explicit instruction. We explore how cognitive development, social environment, and neurological factors influence the ability to acquire languages at this stage. The study compares L1 and L2 acquisition processes and assesses whether the age range offers a critical or sensitive period for language learning. Data was collected through observation and testing of linguistic competencies in children learning under different conditions. Our findings suggest that children within this age range demonstrate high neuroplasticity, enabling relatively smooth L2 acquisition alongside L1 development, but with notable differences in grammar mastery and accent retention.